Pierwowzór XV-wiecznego malowidła z tłocznią mistyczną w krakowskim krużganku klasztoru oo. Franciszkanów - Soćko, Adam (Artium Quaestiones, 2024)
The paper is intended to supplement Helena Małkiewiczówna’s (1972) deliberations on the mural depiction of Christ in the winepress, located in the cloisters of the Franciscan friary in Kraków (c. 1440). This multipart painting has been the subject of comprehensive, monumental, erudite studies accounting for its iconography and theological messages, as well as the historical context elucidating the circumstances of its creation. However, one aspect which has not been fully recognised is the origin of the painting’s composition. The monographer declared the Krakovian mural unique and sought its inspiration in literary works. Michał Janocha pointed to the work’s close connections with two older murals extant in Brzeg and Krzyżowice (1418–28), which, like the Kraków painting, illustrated complex theological messages with an anti-Hussite purport. The thesis assumes the painting’s direct relationship to a sculptural composition: the tympanum in the northern portal of the Church of the Mother of God before Týn in Prague (c. 1370). During the times of the Hussite Revolution, the church became the centre of activity for Utraquists, who constituted moderate faction of the Czech heretics. From this observation there also follows the hypothesis of Franciscan intermediation in transmitting the pictorial pattern, which most likely took place during the Order’s provincial chapter in Kraków in 1436.